Experimental Investigation of a Novel Formulation of a Cyanoacrylate-Based Adhesive for Self-Healing Concrete Technologies - De Nardi, Cristina; Gardner, Diane; Cazzador, Giulia; Cristofori, Davide; Ronchin, Lucio; Vavasori, Andrea; Jefferson, Tony (Frontiers in Built Environment, 2021)
The selection of an appropriate healing agent is critical to the success of vascular and mini-vascular networks. In self-healing concrete technology, commercially available cyanoacrylate (CA) adhesives have been shown to produce good strength recoveries; however, their rapid curing rate and short shelf-life make them unsuitable for site application. The aim of this study was to develop a modified cyanoacrylate (n-CA) with an extended shelf-life suitable for incorporation in a self-healing system. A series of n-CAs were formed from a commercial Ethyl Cyanoacrylate adhesive mixed with acrylic acid (AA) and nitro-anthraquinone (nAq) in varying ratios. When encapsulated within 3D printed mini-vascular networks (MVNs), the n-CAs remained dormant in liquid form for up to 5 days. The contact angle between the n-CAs and the cement mortar substrate, as measured via the sessile drop technique, decreased significantly with increasing AA content. The mechanical properties (bond strength) and the polymerization hardening of the n-CAs were evaluated over a curing period of 7 to 21 days, via a series of pull-off tests using cement mortar cubes. The 4:1:02 (CA:AA:nAq) n-CA formulation showed a significant increase in bond strength from 14 to 21 days, with a ceiling value of 2.6 MPa, whilst the 2:1 (CA:AA) n-CA formulation exhibited a good bond strength after 21 days (1 MPa). Nuclear Magnetic Resonance (NMR) conducted on the n-CAs suggested the formation of several new polymeric species, whilst differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) on the pre- and post-printed MVN material confirmed no significant changes in chemistry with no evidence of polymer degradation. Considered together, the experimental results show the potential for different n-CA formulations to act efficiently as a healing agent.